2021
DOI: 10.21927/jnki.2021.9(1).29-38
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise mat pilates on pain scale, anxiety, heart rate frequency in adolescent principle with primary dismenorhea in Surakarta

Abstract: <p><strong><em>Background:</em></strong><em> During menstruation, there is an imbalance in the hormone progesterone which causes pain or is often called dysmenorrhea. A general percentage of 50–60% of women manage dysmenorrhea using analgetic drugs. Pilates exercise is aimed at producing natural, correct, and efficient motion. It is a stretching and strengthening exercise in the core area, namely the area between the pelvic, abdomen, and back which has the aim of increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…Again, Chang E et al (2018) (32) , elaborated that Pilates stabilization exercises and kinesio taping are effective in decreasing dysmenorrhea in female university students. Furthermore, the present findings were in congruence with, Gopagar M and Devi P (2020) (33) , Cahyanto E et al (2021) (34) , and Purba R et al (2021) (35) , who investigate the effect of Bosu Pilates, Mat Pilates and Pemberian Pilates exercises respectively on primary dysmenorrhea and declared that these exercises significantly reduce the degree of the dysmenorrhea. Despite none of these studies conducted in Egypt, they have the same findings of our study as exercises increase vasodilatation, release of endogenous especially beta endorphins and suppress prostaglandins subsequently shutting of blood flow from viscera resulting in less pelvic congestion and relieving pain as well as hormonal balance resulting in decline of dysmenorrheal intensity.…”
Section: Discussionsupporting
confidence: 90%
“…Again, Chang E et al (2018) (32) , elaborated that Pilates stabilization exercises and kinesio taping are effective in decreasing dysmenorrhea in female university students. Furthermore, the present findings were in congruence with, Gopagar M and Devi P (2020) (33) , Cahyanto E et al (2021) (34) , and Purba R et al (2021) (35) , who investigate the effect of Bosu Pilates, Mat Pilates and Pemberian Pilates exercises respectively on primary dysmenorrhea and declared that these exercises significantly reduce the degree of the dysmenorrhea. Despite none of these studies conducted in Egypt, they have the same findings of our study as exercises increase vasodilatation, release of endogenous especially beta endorphins and suppress prostaglandins subsequently shutting of blood flow from viscera resulting in less pelvic congestion and relieving pain as well as hormonal balance resulting in decline of dysmenorrheal intensity.…”
Section: Discussionsupporting
confidence: 90%
“…Average score of emesis gravidarum decreases over four days using lemon aromatherapy I (Kia, 2013). It is also in line with research conducted by Erick et al by observing the use of non-pharmacological treatments in women to eliminate emesis gravidarum (Cahyanto et al, 2020). The results showed that 40% of women use lemon aroma to relieve nausea vomiting, and more than half of those who have used it say it is effective (al Cidadapi, 2016).…”
Section: Introductionsupporting
confidence: 75%
“…As the interns gradually master knowledge, the teachers should gradually reduce guidance and finally provide interns with the opportunity to use new knowledge to solve variant problems [ 18 ]. The so-called variant problem was to change the problem situation around the teaching goal to make the interns follow suit [ 19 ]. (5) Convergence and integration.…”
Section: Methodsmentioning
confidence: 99%
“…e so-called variant problem was to change the problem situation around the teaching goal to make the interns follow suit [19]. ( 5) Convergence and integration.…”
Section: Methodsmentioning
confidence: 99%